Sri Lankan Discourses of Ethno-Nationalism and Religious Fundamentalism - Sivaloganathan, Myra (My University, 2017)
In this thesis, I argue that discourses of victimhood, victory, and xenophobia underpin both Sinhalese and Tamil nationalist and religious fundamentalist movements. Ethnic discourse has allowed citizens to affirm collective ideals in the face of disparate experiences, reclaim power and autonomy in contexts of fundamental instability, but has also deepened ethnic divides in the post-war era. In the first chapter, I argue that mutually exclusive narratives of victimhood lie at the root of ethnic solitudes, and provide barriers to mechanisms of transitional justice and memorialization. The second chapter includes an analysis of the politicization of mythic figures and events from the Rāmāyaṇa and Mahāvaṃsa in nationalist discourses of victory, supremacy, and legacy. Finally, in the third chapter, I explore the Liberation Tiger of Tamil Eelam’s (LTTE) rhetoric and symbolism, and contend that a xenophobic discourse of terrorism has been imposed and transferred from Tamil to Muslim minorities. Ultimately, these discourses prevent Sri Lankans from embracing a multi-ethnic and multi-religious nationality, and hinder efforts at transitional justice. By shedding light on the discourses underlying popular nationalist movements, I hope to promote understanding and further post-war reconciliation between ethnic groups in Sri Lanka.
Keywords: Sri Lanka; Discourse; Buddhism; Theravada Buddhism; Bodu Bala Sena; Siva Senai; Anthropology; Religious Studies; Religion; Mahavamsa; Ravana; Ravana Balaya; Sinhalese; Tamil; LTTE; Tamil Tigers; Xenophobia; Islamophobia; Religious fundamentalism; Nationalism; Victimhood; Victory; Transitional justice; Memorialization